Digital Transformation of Da'wah Management: Analysis of the Effectiveness of Online Application Utilization DAI Coordination in Era Society 5.0 - Muharram (CV Naskah Aceh, 2025)
While digital technology sometimes offers efficiency, in practice, coordination between preachers is often hampered. Many fail to utilize online applications optimally, resulting in inefficiencies, overlapping programs, and poorly coordinated da'wah messages in the digital space. This type of research uses a library research approach . The data sources in this study are secondary and classified into three main types, namely: books, scientific journal articles, and research reports. The results of the study indicate that: 1). From the pulpit to the digital platform: the reconstruction of the role and method of da'wah in the era of society 5.0 is that the role of da'wah shifts from conventional orators to digital content managers. Da'wah methods evolve from face-to-face lectures to participatory forms such as podcasts, short videos, and live streaming , which are more in line with the characteristics of a digital society. 2). Measuring effectiveness: analysis of the contribution of chat applications, task management, and social media in da'wah coordination is that chat applications act as the backbone of real-time communication, task management applications improve program planning and accountability, while social media doubles as a tool for dissemination and content coordination. The synergy of the three significantly increases the efficiency and effectiveness of coordination. 3). The challenge of integration: addressing the disparity in digital literacy and maintaining the authenticity of da'wah in cyberspace is that there are two main challenges: the digital literacy gap among da'i (preachers) and the risk of da'wah messages being reduced to shallow content due to algorithmic pressure. Maintaining the authenticity of the message remains a key principle that must not be sacrificed.